2018
DOI: 10.1590/2317-1545v40n3199428
|View full text |Cite
|
Sign up to set email alerts
|

Physical, physiological and anatomical changes in Erythrina speciosa Andrews seeds from different seasons related to the dormancy degree

Abstract: Dormancy, a process that allows seeds to survive in adverse environments, needs to be broken for germination to start, for example, by the disruption of the impermeable layer of seeds. Mature seeds of Erythrina speciosa present seed coat impermeability, whose degree depends on the year of production. The objective of this study was to analyze the physical, physiological, anatomical, and ultrastructural seed coat modifications, according to the environmental conditions in which seeds were produced, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 18 publications
(19 reference statements)
5
18
0
Order By: Relevance
“…Even dormancy could be seen as one more of the lines, or response surfaces, with possibilities of changes depending on the environment, regardless of the separation into orthodox and recalcitrant. Thus, dormancy must be separated from specific stages of maturation, as proposed by , and may even be induced (Molizane et al, 2018). Therefore, unlike the previous models, which considered dispersed recalcitrant seeds as effectively mature, and that always found several exceptions, all the behaviors are contemplated in this model.…”
Section: Age (Days After Anthesis)mentioning
confidence: 99%
“…Even dormancy could be seen as one more of the lines, or response surfaces, with possibilities of changes depending on the environment, regardless of the separation into orthodox and recalcitrant. Thus, dormancy must be separated from specific stages of maturation, as proposed by , and may even be induced (Molizane et al, 2018). Therefore, unlike the previous models, which considered dispersed recalcitrant seeds as effectively mature, and that always found several exceptions, all the behaviors are contemplated in this model.…”
Section: Age (Days After Anthesis)mentioning
confidence: 99%
“…According to Delgado et al (2015), seeds of Erythrina speciosa Andrews (Leguminosae, Papilionoideae) exhibit physical dormancy. However, Molizane et al (2018) demonstrated that the proportion of seeds in physical dormancy in this species could vary according to parental environmental conditions. According to these authors, in years when there is a higher water deficit during seed formation, only 2 % of produced seeds germinated without scarification.…”
mentioning
confidence: 91%
“…According to these authors, in years when there is a higher water deficit during seed formation, only 2 % of produced seeds germinated without scarification. In years with greater availability of water during seed formation, germination reached 40 % without dormancy breaking treatments (Molizane et al 2018). In addition, Magalhães (2016) observed a difference in the imbibition of E. speciosa seeds when analyzed immediately after dispersion and after storage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, environmental conditions under which the plant is subjected during seed production may interfere with the establishment of physical dormancy (Molizane et al 2018;Penfield & MacGregor, 2017). Germination of Erythrina speciosa seeds from the same population followed for six years showed strong interannual variation (Molizane et al 2018). The authors attribute this oscillation in germination over the years to different degrees of dormancy, correlating it to environmental conditions (i.e.…”
Section: Resultsmentioning
confidence: 99%